Ecological adaptations and commensal evolution of the Polynoidae (Polychaeta) in the Southwest Indian Ocean Ridge: A phylogenetic approach. (March 2017) - Serpetti, Natalia; Taylor, M.L.; Brennan, D.; Green, D.H.; Rogers, A.D.; Paterson, G.L.J.; Narayanaswamy, B.E.
Abstract: The polychaete family polynoid is very large and includes a high diversity of behaviours, including numerous examples of commensal species. The comparison between free-living and commensal behaviours and the evolution of the relationships between commensal species and their hosts are valuable case studies of ecological adaptations. Deep-sea species of Polynoidae were sampled at four seamounts in the Southwest Indian Ridge and twenty specimens from seven species were selected to be analysed. Among them, there were free-living species, living within the three-dimensional framework of cold-water coral reefs, on coral rubble and on mobile sediments, and commensal species, associated with octocorals, hydrocorals (stylasterids), antipatharians and echinoderms (holothurian and ophiuroids). We analysed two mitochondrial (COI, 16S) and two nuclear (18S, 28S) ribosomal genetic markers and their combined sequences were compared with other Genbank sequences to assess the taxonomic relationships within the species under study, and the potential role of hosts in speciation processes. Most basal species of the sub-family Polynoinae are obligate symbionts showing specific morphological adaptations. Obligate and facultative commensal species and free-living species have evolved a number of times, although, according to our results, the obligate coral commensal species appear to be monophyletic.